Pengaruh Budaya Organisasi, Komitmen Organisasi dan Kepuasan Kerja terhadap Organizational Citisenship Behavior Pada Pegawai Kantor Pengadilan Negeri Mataram - Haryati, Putri; Suryatni, Mukmin; Sakti, Dwi Putra Buana (Postgraduate, University of Mataram, 2024)
This research is entitled the influence of organizational culture, organizational commitment and job satisfaction on Organizational Citizenship Behavior of Mataram District Court office employees. Aims to determine the influence of organizational culture, organizational commitment and job satisfaction on organizational citizenship behavior. The type of research used is causal associative research with a quantitative approach. The data collection method used is the census method. The population and respondents in the research were 83 employees of the Mataram District Court office. The analytical tool used is Multiple Linear Regression using SPSS versions 25 and 26. The results of the analysis show that: (1) organizational culture has a positive and significant effect on organizational citizenship behavior (2) organizational commitment has a positive and significant effect on organizational citizenship behavior (3) Job satisfaction has a positive and significant effect on organizational citizenship behavior